2008
DOI: 10.1038/ni1008-1091
|View full text |Cite
|
Sign up to set email alerts
|

The Immunological Genome Project: networks of gene expression in immune cells

Abstract: The Immunological Genome Project combines immunology and computational biology laboratories in an effort to establish a complete 'road map' of gene-expression and regulatory networks in all immune cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

76
1,502
5
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 1,641 publications
(1,642 citation statements)
references
References 18 publications
76
1,502
5
4
Order By: Relevance
“…Previous work by Petrie and colleagues showed that IL-1β and IL-23 are expressed by mTECs at comparable levels to IL-7 42 . Moreover, specific subsets of thymic γδ T cells and a population of CD4 + T cells express high levels of IL-21R, during the appropriate ontological window of time to affect γδ17 development (www.immgen.org) 43 , plus a subset of IL-21 expressing thymocytes was recently reported 44 . Therefore, we assessed whether inhibiting IL-1β, IL21, and IL-23 inputs would interfere with the generation of γδ17 cells in the context of wildtype progenitors in the fetal thymus.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work by Petrie and colleagues showed that IL-1β and IL-23 are expressed by mTECs at comparable levels to IL-7 42 . Moreover, specific subsets of thymic γδ T cells and a population of CD4 + T cells express high levels of IL-21R, during the appropriate ontological window of time to affect γδ17 development (www.immgen.org) 43 , plus a subset of IL-21 expressing thymocytes was recently reported 44 . Therefore, we assessed whether inhibiting IL-1β, IL21, and IL-23 inputs would interfere with the generation of γδ17 cells in the context of wildtype progenitors in the fetal thymus.…”
Section: Resultsmentioning
confidence: 99%
“…Transcripts with the highest level of expression increased in both ALS and aging were compared with data generated by the Immunological Genome (ImmGen) project, a consortium that has mapped gene expression patterns in major classes of immune cell types (Heng & Painter, 2008). The purpose of this analysis was to understand the cellular basis underlying the increased immune and inflammatory response during aging and ALS.…”
Section: Resultsmentioning
confidence: 99%
“…ImmGen, initiated in 2007, is a collaborative group of 15 immunology and computational biology laboratories that have sought to perform, under carefully standardized conditions, a thorough dissection of gene expression in the immune system 7 . In the first phase, the group focused on generating gene expression profiles for primary haematopoietic cells from different anatomical locations that were analysed directly ex vivo at finely defined stages of differentiation.…”
Section: The Consmentioning
confidence: 99%